2006
DOI: 10.1080/16522354.2006.11073438
|View full text |Cite
|
Sign up to set email alerts
|

Doing Digital: An Assessment of the Top 25 U.S. Media Companies and their Digital Strategies

Abstract: This study examines how major U.S. media companies are developing their digital strategies in the context of earlier work on convergence. Through rare interviews with media leaders and other sources, the ways that media corporations have coped with digital innovation following the dot-com crash are explored, including its delivery and the styles of leadership. The authors posit that media firms fall into three categories: leaders, learners and laggards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…The ways in which media organisations contend with the challenges of adapting to digitisation and the internet have been the pivotal issue in many earlier studies (ChanOlmsted & Chang, 2003;Dennis et al, 2006;Küng, Picard, & Towse, 2008;Meikle & Young, 2008) but few have focused specifically on multi-platform strategies. Therefore this article extends a limited body of earlier work (Bennett & Strange, 2014;Sørensen, 2014) by presenting new findings in relation to how the transition to a multi-platform environment is impacting on organisational strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ways in which media organisations contend with the challenges of adapting to digitisation and the internet have been the pivotal issue in many earlier studies (ChanOlmsted & Chang, 2003;Dennis et al, 2006;Küng, Picard, & Towse, 2008;Meikle & Young, 2008) but few have focused specifically on multi-platform strategies. Therefore this article extends a limited body of earlier work (Bennett & Strange, 2014;Sørensen, 2014) by presenting new findings in relation to how the transition to a multi-platform environment is impacting on organisational strategies.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive literature has developed concerning how organisations in media and communications industries have struggled to adapt to advancing technology and, in particular, their responses to digitisation and the internet have provided a focus in many earlier studies (Chan-Olmsted & Chang, 2003;Dennis, Warley, & Sheridan, 2006;Gershon, 2009;Küng, 2008;Küng, Picard & Towse, 2008;Meikle & Young, 2008;Raviola & Gade, 2009). Some earlier studies have focused on multi-platform strategies although typically the context for such analyses is a single sector, for example some looking purely at the experience of newspaper publishers (Goyanes & Dürrenberg, 2014) and others at magazines (Champion, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous earlier studies have concerned themselves with the ways that new communications technologies impact on media markets (Chan-Olmsted, 2006: 251-2;Dennis, Warley and Sheridan, 2006;Küng, 2008;Küng, Picard and Towse, 2008). This research set out to look at the multi-platform strategies in the broad context of the notion of 'creative destruction'.…”
Section: Negotiating Creative Destruction: a Case Study Of Uk Televisionmentioning
confidence: 99%
“…Dennis et al (2006) in a study of strategies of media companies showed that digital technologies effect on operational levels of media firms such as hiring patterns and acquisition of creativity, analytical abilities, and technical knowledge. Khajeheian (2013) studied the commercialization of media entrepreneurs' digital innovations at the level of firms.…”
Section: Suggestions For Further Researchesmentioning
confidence: 99%